Familial cortical dysplasia caused by mutation in the mammalian target of rapamycin regulator NPRL3 - Sim, J.; Scerri, T.; Fanjul-Fernández, M.; Riseley, J.; Gillies, G.; Pope, K.; Van Roozendaal, H.; Heng, Julian; Mandelstam, S.; McGillivray, G.; Macgregor, D.; Kannan, L.; et al. (John Wiley and Son, 2016)
© 2015 American Neurological Association. We describe first cousin sibling pairs with focal epilepsy, one of each pair having focal cortical dysplasia (FCD) IIa. Linkage analysis and whole-exome sequencing identified a heterozygous germline frameshift mutation in the gene encoding nitrogen permease regulator-like 3 (NPRL3). NPRL3 is a component of GAP Activity Towards Rags 1, a negative regulator of the mammalian target of rapamycin complex 1 signaling pathway. Immunostaining of resected brain tissue demonstrated mammalian target of rapamycin activation. Screening of 52 unrelated individuals with FCD identified 2 additional patients with FCDIIa and germline NPRL3 mutations. Similar to DEPDC5, NPRL3 mutations may be considered as causal variants in patients with FCD or magnetic resonance imaging-negative focal epilepsy.